English Flag-Waving: The Politics of Englishness (KULT_online, 2009)
The monograph The Politics of Englishness (2007) by Northern Irish political scientist Arthur Aughey provides a thorough and sound overview of recent discussions of English national identity. In doing so, the author transcends the perspective of political sciences, making the study highly appropriate reading for those in the literary and cultural studies who are invested in the topic. Moreover (and in contrast to many studies by English authors, which tend to be ideologically charged) the author convinces by maintaining a high degree of objectivity when considering this politically charged issue.